Integrated Water Management Practices in Wainganga River Basin: A Case Study of Vidarbha Region, Maharashtra - Ravindra Bhagat (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The present study is Integrated Water Management practices in Wainganga river basin: A case study of Vidarbha Region, Maharashtra, using by geographical information system (GIS) and remote sensing (RS) techniques. The study will be based on secondary data. Then all the collected data were scrutinized carefully and recorded in master sheets. Runoff is one of the most important hydrological variables used in most of the water resources applications. Watershed based planning and management requires thorough understanding hydrological processes and accurate estimation of runoff. The determination of runoff at micro level is essential to address water conservation practices in a watershed. The information pertaining to occurrence of run off further helps in integrated water management practices such as prioritizing watersheds, erosion control and selection of sites for conservation measures. The monsoon rains in district are concentrated in the four months from June to September and receive 90.81% rainfall, post-monsoon 1.86% pre-monsoon 4.83% and winter 2.48%. Sandy red soil has covered 31% area; median black soil has covered 47% and Lomi red soil 22% covered the area of district. There are 580 large and 13,758 small and medium sized lakes in the district. The percentage of total area under forest 12.25%, especially during 2001 to 2011 periods it was in Bhandara (12.33%), Mohadi (19.89%), Tumsar (13.27%), Lakhani (11.13%) and Lakhandur (16.24%) decreased on large scale. The aim of this present study was to evaluate integrated management system in the Wainganga River basin that have been delineated based on the geospatial environment parameters with appropriate weights in GIS and RS techniques.
Keywords: Water Management; catchment; rainfall runoff relationship